Managing acute central nervous system infections in the UK adult intensive care unit in the wake of UK encephalitis guidelines. (November 2015) - Stoeter, DJ; Michael, BD; Solomon, T; Poole, L
The acute central nervous system infections meningitis and encephalitis commonly require management on intensive care units. The clinical features often overlap and in the acute phase–altered consciousness and seizures may also need to be managed. In April 2012, the first UK national guideline for the management of suspected viral encephalitis was published by the British Infection Association and Association of British Neurologists, and other key stakeholders, and included a simple management algorithm. The new guideline results from evidence demonstrating a number of common oversights in the standard management of suspected viral encephalitis in many settings. In combination with British Infection Association meningitis guidelines, evidence-based approaches now exist to facilitate the non-expert managing patients with suspected central nervous system infections. Here we bring together these guidelines and the supporting evidence applicable for intensivists into a single resource.